Promoting Community Participation in Improving Maternal and Neonatal Health in Ntcheu District, Malawi: Suggestions for the First National Community Health Strategy - Makata, MacArthur; Narattharaksa, Kanida; Briggs, David (NU Journal of Nursing and Health Sciences, 2022)
Malawi, a developing country in southern Africa, adopted its first National Community Health Strategy 2017-2022 to strengthen community health through a harmonized and integrated community approach. The challenges faced with community participation in maternal and neonatal health (MNH) contribute to the country's health system failures threatening chances of achieving the sustainable development goals targets in the area. A qualitative case study utilizing a phenomenological approach was used to suit the exploration of challenges in promoting community participation to improve MNH. The study was conducted in Ntcheu district, the central region of Malawi. Thirty-five respondents were purposively sampled from functioning teams and committees at various levels within the district health system.The challenges were explored by using key informant interviews of health managers in Ntcheu district, Malawi.Data was manually analyzed using thematic analysis technique and processed and cleaned using Microsoft excel and word processing programs. The study found the issues presenting as challenges associo-cultural differences detrimental to MNH, problems with community health volunteering, and inadequate health care workers and facilities to respond to community needs. The study recommended integrated health promotion with well-composed MNH messages that capture all sections of society to deal with the socio-cultural issues. The study reinforced the need for good coordination and adequate support for community health volunteer activities. Resource mobilization and building more capacity of the health workforce and facilities to improve service provision are needed to adequately respond to the community needs.